Alzheimer’s Disease and Paraoxonase 1 (PON1) Gene Polymorphisms - Saeidi, Mohsen (Open Biochem J, 2017)
BACKGROUND: Some studies have indicated that human paraoxonase 1 (PON1) activity shows a polymorphic distribution. The aim of this study was to determine the distribution of PON1 polymorphism in patients with Alzheimer’s disease in Gorgan and compare it with a healthy control group. METHOD: The study included 100 healthy individuals and 50 patients. Enzyme activity and genetic polymorphism of PON1 were determined. RESULT: There were significant differences in distribution of genotypes and alleles among patients and control group. The most common genotype was CT in patients and control group, while the most frequent alleles were T and C in patients and controls, respectively. There was a statistically significant variation between serum PON1 activity and –108C> T polymorphism. The highest PON1 enzyme activities in the patients and controls were found in CC, while lower enzyme activities were seen in CT and TT genotypes in both genders and age groups. CONCLUSION: Onset of Alzheimer’s disease may depend on different polymorphisms of the PON1 enzyme. Late or early-onset of Alzheimer’s disease may also depend on age and gender distribution, especially for arylesterase enzyme. Further studies on polymorphism of the enzyme are necessary for interpretation of possible polymorphic effects of enzyme on PON1 activity in humans.